HUBUNGAN KOORDINASI MATA KAKI DAN POWER OTOT TUNGKAI DENGAN ACCURACY SHOOTING SEPAKBOLA PADA SISWA SMK TELKOM PEKANBARU - Virdiansyah Virdiansyah; Ramadi Ramadi; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The problem of this research is not optimal of coordination eye leg muscle power and leg muscle power leg to do shooting football. This research was conducted to determine whether there is relationship of coodination of eye and leg muscle power leg with shooting accuracy on the football on student of SMK Telkom Pekanbaru. Sample in this study is the football on student of SMK Telkom Pekanbaru and totaled 18 people. The technique to collecting of sample was ( total sampling). The instrument of this research is Leg eye coordination test, which aims to measure eye coordination and test vertical power test jump which aims to measure the skill of shooting a ball. After that processing data with statistic, to test for normality with lilifor test at significant level α0,05. Based on the result of research, it can be concluded as follows. of the result obtained coordination eye leg has no significant connection with teh result accuracy shooting on football on student of SMK Telkom Pekanbaru because , rcount(0,437) > rtab (0,468), Of the result obtained leg muscle power has no significant relationship with the result accuracy shooting on the football on student of SMK Telkom Pekanbaru rcount(0,098) < rtab (0,468), there is significant relationship together between coordination eye leg and leg muscle power against result acuracy shooting on fotball on student of SMK Telkom Pekanbaru because Rcount (0,479) >Rtab (0,468).Key words : Coordination Eye Leg, Leg Muscle Power, Accuracy Shooting.